Fotodectores de Monocamada de Dissulfeto de Molibdênio (MoS2) - Andreij de Carvalho Gadelha (2015)
MoS2, as graphite, is a layered crystal, with a monolayer counterpart obtained by mechanical exfoliation. Unlike graphene, it has a direct band gap, so it can be applied in optoeletronics. Taking advantage of this potential, we developed field-effect transistors, based on monolayer MoS2, to study its photocurrent properties. We investigate photocurrents in MoS2 by using laser excitation with energy above the gap and with sub-band energy. In the first case, we achieved high photocurrents, with long decay time. These results point out that MoS2 possess high sensitivity to light with energy larger than the band gap energy.In the second case, however, inter-band excitation is not possible but our devices show photoresponse, with low gains - which suggest the presence of defect states inside the gap. The measurements were carried out at diverse atmospheric and temperature conditions, andwe observed the photocurrent behavior depends on these imposed contitions. Our results point out that the photocurrent in MoS2 is governed by defects states inside the band gap. Those would take account for the sub-band gap photocurrent.